Criminal justice responses to maternal filicide : judging the failed mother - Milne, Emma (Emerald Publishing Limited, 2021)
Analysis of criminal cases reveals that women suspected of killing their newborn children are some of the most vulnerable in our society and that infanticide is not just a historical issue but one that has modern implications. While women are less likely to commit violent crime, maternal infant homicide is an enduring form of offending that needs to be understood in a wider social context. In Criminal Justice Responses to Maternal Filicide, Milne provides a comprehensive analysis of conviction outcomes through court transcripts of 15 criminal cases in England and Wales during 2010 to 2019. Drawing on feminist theories of responsibilisation and 'gendered harm', she critically reflects on the gendered nature of criminal justice's responses to suspected infanticide. This contemporary study makes a novel contribution to the fields of law, criminology and gender studies, arguing that through its inability to recognise the vulnerable position of accused women, and respond accordingly, the application of law reflects wider social judgments of pregnant women and mothers who challenge or fail to fulfil ideals of motherhood.